Environmental management system and financial performance - Ong, Tze San; Teh, Boon Heng; Ng, Sin Huei; Soh, Wei Ni (Faculty Economics & Administration, University of Malaya, 2016)
The paper aims to explore the relationship between ISO 14001 certification and a company's financial performance to investigate whether the certification to ISO 14001 environmental management standard has benefited the company's financial performance or not. Using Malaysia as the research context, the results of a linear regression analysis show that firms with above-average performance have a greater tendency to pursue ISO 14001 certification. The findings also indicate that there is a significant relationship between ISO14001 certification and a company's financial performance in an emerging economy context. The reason is the adoption of ISO 14001 standard does offers many benefits to companies, such as greater reputation and brand awareness on one hand, and higher sales and investors' confidence on the other. The ISO 14001 certification helps to develop a better system which leads to costs reduction and revenue increase in the long run.